Complications of Local Anesthesia - Stutishree Tripathy (Institute of Medico-legal Publications Pvt Ltd, 2020)
This chapter is presenting the local and systemic complications associated with the local anesthetics usedin oral and maxillofacial surgery. The prevention of complications and management method are alsogiven importance. Dental procedures are frequently performed under local anesthesia; thus, drug-relatedcomplications often come across. It is mandatory to have a preoperative evaluation of the patient andchoosing the proper local anesthetic agents.